2002
DOI: 10.1080/014215901200901041
|View full text |Cite
|
Sign up to set email alerts
|

Which common clinical conditions should medical students be able to manage by graduation? A perspective from Australian interns

Abstract: The objectives of the study were to report the development of a core curriculum that details the clinical conditions medical students should be able to manage upon graduation; and to canvass the opinion of interns (first-year postgraduate doctors) regarding their perceptions of the level of skill required to manage each condition. Literature relating to core curriculum development and training of junior medical officers was reviewed and stakeholders in the education and training of medical students and junior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The difficult nature of the transition from medical school to internship is well documented, as is the lack of intern preparedness as reported by students and their supervisors’ [14,18,19]. To improve the transition from medical school to internship, UNSW developed a PRINT course that was first implemented in 2007 for students who had learned within a traditional content-based curriculum, and continued for subsequent student cohorts who had enrolled in a new outcomes-based program, that places importance on development of generic as well as clinical capabilities [6,24].…”
Section: Discussionmentioning
confidence: 99%
“…The difficult nature of the transition from medical school to internship is well documented, as is the lack of intern preparedness as reported by students and their supervisors’ [14,18,19]. To improve the transition from medical school to internship, UNSW developed a PRINT course that was first implemented in 2007 for students who had learned within a traditional content-based curriculum, and continued for subsequent student cohorts who had enrolled in a new outcomes-based program, that places importance on development of generic as well as clinical capabilities [6,24].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the level at which interns functioned in these hospitals was very high when compared to other countries. 7,13,24 This implies that, with sufficient support and supervision, the combination of university training and an internship year is adequately preparing junior doctors for independent practice in this region. It may be of interest to repeat this exercise in a couple of years, when all universities will follow a new format of teaching with greater focus on practical skills.…”
Section: Resultsmentioning
confidence: 99%
“…An exploration of the barriers and difficulties involved in the learning of clinical skills will be made. 22,23,24,25,26,27,28,29,30,31,32,33,34,35 Method…”
Section: Literaturementioning
confidence: 99%
“…A recent survey of 400 Australian interns suggests that they are able to nominate and prioritise areas that they feel are required for intern practice (Rolfe et al, 2000). However, they may not be aware of the tasks that will confront them as clinicians.…”
Section: Incorporating Consumers' Viewsmentioning
confidence: 99%